2022
DOI: 10.3389/fpsyg.2022.942535
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of COVID-19 pandemic-related changes in social interactions on preschoolers' emotion labeling

Abstract: During the COVID-19 pandemic people were increasingly obliged to wear facial masks and to reduce the number of people they met in person. In this study, we asked how these changes in social interactions are associated with young children's emotional development, specifically their emotion recognition via the labeling of emotions. Preschoolers labeled emotional facial expressions of adults (Adult Faces Task) and children (Child Faces Task) in fully visible faces. In addition, we assessed children's COVID-19-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
1
0
3
Order By: Relevance
“…Apesar das dificuldades impostas pelo uso de máscaras faciais, é notável a capacidade das crianças e adolescentes em adaptarem-se a essa nova realidade. Um estudo experimental realizado na Alemanha, durante a pandemia de COVID-19, revelou que as crianças préescolares foram capazes de reconhecer corretamente as expressões de medo mesmo diante do uso de máscaras, indicando a resiliência de sua capacidade em interpretar emoções (WERMELINGER et al, 2022).…”
Section: Revisão Bibliográficaunclassified
See 2 more Smart Citations
“…Apesar das dificuldades impostas pelo uso de máscaras faciais, é notável a capacidade das crianças e adolescentes em adaptarem-se a essa nova realidade. Um estudo experimental realizado na Alemanha, durante a pandemia de COVID-19, revelou que as crianças préescolares foram capazes de reconhecer corretamente as expressões de medo mesmo diante do uso de máscaras, indicando a resiliência de sua capacidade em interpretar emoções (WERMELINGER et al, 2022).…”
Section: Revisão Bibliográficaunclassified
“…Estudos têm destacado que o uso de máscaras pode limitar a capacidade desses jovens em interpretar expressões emocionais, afetando, assim, sua interação social. Além disso, tem-se observado que o uso contínuo de máscaras pode ter repercussões na saúde mental dessa faixa etária, resultando em um aumento do estresse e da ansiedade (CRIMON et al, 2022;FREIBERG et al, 2021;WERMELINGER et al, 2022).…”
Section: Considerações Finaisunclassified
See 1 more Smart Citation
“…Recently, studies have examined the influence of masks on emotion recognition (e.g., Barrick et al, 2020;Calbi et al, 2021;Carbon, 2020;Marini et al, 2021;Pazhoohi et al, 2021;Ruba & Pollak, 2020;Wermelinger, Moersdorf, Ammann, et al, 2022). Calbi et al (2021) showed that adults correctly recognized emotions in faces with masks and they did not attribute more negative valence to faces with masks compared to faces wearing scarfs that similarly covered the mouth.…”
Section: Emotion Recognition During the Covid-19 Pandemicmentioning
confidence: 99%